IMPROVING INVESTMENT ACTIVITIES THROUGH ISLAMIC BANKS (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the theoretical and legal framework for financing investment activities through Islamic banks, the organizational system, as well as individual approaches to improving the theoretical basis for the implementation of Islamic banking instruments in our country.